Social capital and members’ loyalty in agricultural producer organizations in Poland - Chlebicka, Aleksandra; Pietrzak, Michał (Turystyka i Rozwój Regionalny, 2022)
The aim of the paper is to explain the importance of social capital for the survival and growth of producer organizations in agriculture. Our main research question concerns the underlying causes of lack of loyalty of growers-members to producer organizations. We link the problem of outside individual sales to deficits in necessary formal institutions safeguarding against member disloyalty. To assess the scale of the problem and to identify ways to counter this opportunistic behaviour, we use data from direct interviews with CEOs of 65 fruit and vegetable producer organizations (POs). We proved that in the smallest POs the occurrence of opportunism was completely eliminated by informal institutions related to bonding social capital. Conversely, in larger POs weak bridging-type relationships proved insufficient to build trust - producers were highly susceptible to outside incentives. Moreover, the use of formal institutions to protect from opportunism turned out to be surprisingly low in medium and large entities.